THE MEANING OF QUALITY OF ACCOUNTING LEARNING IN THE PANDEMIC TIME COVID 19 (INTERPRETATIVE STUDY AT THE HEAD OF PTM ACCOUNTING STUDY PROGRAM IN INDONESIA) - Sarwenda Biduri; Sigit Hermawan; Wiwit Hariyanto (Berkala Akuntansi dan Keuangan Indonesia, 2021)
The Covid 19 pandemic that has occurred since December 2019 until now requires all teaching and learning activities for students to be temporarily carried out online from home, this learning is very different from conventional learning that occurs on campus, lecturers and students do not face directly but are separated. by distance that allows lecturers and students to be in different places, the positive effect of this learning really helps the continuity of the learning process during a pandemic like this. Lecturers and students must take advantage of communication media and social media as data storage media that can be used to record quality learning activities. The purpose of this research is, to find out how the quality of learning in accounting lecturers during the Covid 19 pandemic, to find out how the availability of IT and E-Learning helps in the quality of learning for accounting lecturers during the Covid 19 pandemic, to find out how the accounting program stakeholder strategy is to improve the quality of learning during the covid pandemic 19.